Sintomas e interacción familiar - Sluzki, Carlos E. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Symptoms have an interactional valence inasmuch as they affect and promote behavior in other persons, even though the epistemological confusion between the “cause-effect” relation and intentionality leads to their not being understood in this manner. Symptoms of one member of the family can act as the axis of the functioning family and reinforce or modify interpersonal stereotypes. However, there is a tendency on the part of psychotherapists—of individuals and even of families—to understand the patient as a victim of a “pathogenic family”, disregarding the fact that in an interactional system the phenomena are multidetermined in a dialectic manner. It is stated that a source of misunderstanding comes from a conceptual transposition of etiopathogenic models—explanatory—to therapeutic models—operational.